2015
DOI: 10.5430/ijfr.v7n1p135
|View full text |Cite
|
Sign up to set email alerts
|

Large Shareholder’s Identity and Stock Price Synchronicity: Evidence from a MENA Market

Abstract: This paper investigates the association between large shareholder's identity and stock price synchronicity in a country where investor protection is weak. Results show that stock prices in Jordan have synchronous behavior especially when the firm is large, consistent with previous empirical evidence on stock price behavior in low per capita GDP countries. Most of the public corporations are owned and controlled by families. In most of the family-controlled firms, the controlling family is also involved in firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Additionally, controlling families are involved in a firm's management, which gives them great discretion over their assets and facilitates the expropriation of minority shareholders' rights (La Porta et al. , 1999; Bino et al. , 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, controlling families are involved in a firm's management, which gives them great discretion over their assets and facilitates the expropriation of minority shareholders' rights (La Porta et al. , 1999; Bino et al. , 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that large shareholders may improve firm's corporate governance mechanisms and provide effective monitoring of management actions (Shleifer and Vishny, 1997). However, the absence of legal protection enables large shareholders to expropriate minority shareholders' rights and extract private benefits in an attempt to maximize their utility rather than monitor the firm's management and maximize firm value (Abu-Ghunmi et al, 2015;Bino et al, 2016). We argue that the impact of large shareholders on agency costs depends on the extent to which a firm's management and ownership are separate.…”
Section: Datamentioning
confidence: 99%
“…There is a limited amount of literature that examines stock price synchronicity using Jordanian data. Bino et al (2016) examined the effect of a firm's ownership structure on stock price synchronicity, finding that stock prices in Jordan have synchronous behaviour, especially when the firm is large or owned by the government; family-owned firms, however, record lower stock price synchronicity than those of firms with wider ownership.…”
Section: The Jordanian Contextmentioning
confidence: 99%
“…However, the level of the board of directors' errors and effectiveness in inspecting managers is based on the board size and board composition. Bino et al (2016) examined the effect of large shareholders' identity and stock price synchronicity in Jordan, a country with weak investor protection, and found that large Jordanian firms are more synchronous than small firms, as well as that the family-controlled firms record lower stock price synchronicity than do firms with a wider ownership. Fan and Wong (2005) documented that the Big Four auditors, as a proxy for corporate governance measurement, play big roles in emerging markets with highly concentrated ownership structures.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation